2007
DOI: 10.1080/17453670710014608
|View full text |Cite
|
Sign up to set email alerts
|

Women with low-energy fracture should be investigated for osteoporosis

Abstract: Introduction Treatment of osteoporosis is becoming more effective, but methods to identify patients who are most suitable for investigation and treatment are still being debated. Should any type of fracture have higher priority for investigation of osteoporosis than any other? Is the number of previous fractures useful information?Material and methods We investigated 303 consecutive women patients between 55 and 75 years of age who had a newly diagnosed low-energy fracture. They answered a questionnaire on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 35 publications
2
36
1
1
Order By: Relevance
“…The total prevalence of low BMD (T-score ≤−2.0 SD) and osteoporosis (T-score ≤−2.5 SD) in our study is similar to findings in two previous studies on women [25,26]. Löfman et al [25] found T-scores <−2.0 SD in 53% and <−2.5 SD (osteoporosis) in 37% at total hip or spine in 171 Swedish women (mean age, 67 years) with distal radius fractures while McLellan et al [26] diagnosed osteoporosis at the same measurement sites in 41% of the 420 Glasgow women aged 50 years and older with similar fractures.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The total prevalence of low BMD (T-score ≤−2.0 SD) and osteoporosis (T-score ≤−2.5 SD) in our study is similar to findings in two previous studies on women [25,26]. Löfman et al [25] found T-scores <−2.0 SD in 53% and <−2.5 SD (osteoporosis) in 37% at total hip or spine in 171 Swedish women (mean age, 67 years) with distal radius fractures while McLellan et al [26] diagnosed osteoporosis at the same measurement sites in 41% of the 420 Glasgow women aged 50 years and older with similar fractures.…”
Section: Discussionsupporting
confidence: 94%
“…In previous studies, lower BMD in patients with a distal radius fracture compared with controls has been reported in both men [23] and women [14,24,25,37]. However, in two studies where heel BMD was used, no differences were found between patients with a distal radius fracture and controls [38,39].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A high percentage of women with low-energy distal radius fractures have osteoporosis [1] and bone mineral density (BMD) has been found to be lower in distal radius fractures patients compared to age-matched controls and bone density reference populations [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…11 These also correspond to the fourth most frequent fracture during the osteoporosis period, responsible for 12% of all fractures. 12,13 According to Maravic et al 14 , in France, each humerus fracture of osteoporotic origin, generates individual annual costs around US$4,000. Zoledronate, which acts by inhibiting the osteoclastic action and, consequently, decreasing bone resorption, 15 can be used in the prophylaxis of fractures caused by osteoporosis.…”
Section: Linear Regression Analysismentioning
confidence: 99%